A crise do poder e da obediência na vida religiosa consagrada feminina: uma abordagem psicossocial e político-religiosa. - Ferreira, Luzia Valladão (2021)
This thesis reflects about power and obedience in Consecrated Women’s Religious Life and its bond with Christian service according to the principles of co-responsibility at psychosocial and political-religious levels. The object of the research is the reflection on how the obstacles happen and the causes that can generate crises, conflicts or difficulties in managing a community of consecrated religious. In this sense, it deals with fundamentals about the formation of subjectivities focusing on the figure of the woman with her vulnerabilities; of theological presuppositions on the doctrine of the Catholic Church on the vow of obedience; the need for technical skill for leaders; in addition to confronting with the lay world, the perception of how crises are experienced in the conventual environment. As a specific group incorporated into religious world, part of Catholic Christianity, life and work, both with a single sense have a transcendent meaning. Having experienced this situation and felt the difficulties of convent management, my interest in the subject arose. Everything experienced in this context is permeated with symbologies that exercise power, sometimes without a clear perception of some of the participants, including those who exercise power or authority. In developing this thesis, questions were anchored in Pierre Bourdieu’s theory on symbolic violence, present in different fields. Co-responsibility is a important fator among the members or the community, but it derives from the well -or poorly- formed subjectivities and/or technical unpreparedness of managers. Thus, in the view of different authors such as Anthony Giddens, Lev Vygotsky, Soren Kierkegaard, and others, attention was paid to the formation of subjectivities with sociological, psychopedagogical and philosophical approaches, in convergence with Bourdieu’s thought. By applying the qualitative methodology, interviews brought to light the practice experienced in the exercise of leadership, revealing it close to or far from what is considered “ideal”. Twelve sisters, missionaries in Northeast Brazil, from different communities were interviewed. The data collected and confirmed by the interviewees were categorized an analyzed, taking into account the conventual structure. Specific formation, goas, difficulties and overcoming were examined as constituents of the exercise in canonical leadership and revealed experienced crises capable, however, of emanating patience, understanding and humility. Bourdieu’s theory offers elements for the understanding of the phenomenon, present in this social field (locus numinosum), permeated by mental structures (habitus), forming beliefs that are structured as indisputable (doxa), called by him as symbolic violence. From this perspective, as a result, we detect that crises are natural to consecrated religious life, such as crises of power and obedience. However, they are different from those of lay organizations because subjectivities are induced to “sublimate” conflicts and differences, which brings humility, resignation, service, obedience, submission.